FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR SEKTOR CONSUMER GOODS - Stella Elvira Saputra; Yuniarwati Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this study was to examine the effect of leverage, net working capital, and capital expenditure on cash holding in manufacturing companies in the consumer goods sector listed on the IDX for the 2019-2021 period. Determination of sample selection by applying the purposive sampling method, which resulted in a total sample of 32 companies in this study that met the qualifications. Hypothesis testing is used with the model using multiple regression analysis. This data was processed with EViews (Econometric Views) student version lite 12 software. The results of this study indicate that leverage has a negative effect on cash holding. While net working capital has no effect on cash holding and capital expenditure has no effect on cash holding.